Calculation of pressure on the shallow-buried twin-tunnel in layered strata. (September 2020) - Lyu, Hai-Min; Shen, Shui-Long; Zhou, Annan; Chen, Ke-Lin
Highlights: The existing approaches for calculating tunnel pressure are reviewed. An analytical approach for calculating the twin-tunnel pressure in layered strata is proposed. The proposed approach is based on limit equilibrium analysis with different failure patterns. The proposed analytical approach was validated by numerical analysis and field data. Relationships among tunnel pressure, strata thicknesses, and rock characteristics were analysed. Abstract: This study proposes a novel analytical approach to calculate tunnel pressure due to the surrounding rock of a twin-tunnel in layered strata. The proposed approach is based on a limit equilibrium analysis that considers different failure patterns (depending on whether failures are located in the upper or lower layers). The proposed approach is adopted for the pressure analysis of the metro twin-tunnels in Chongqing and Fuzhou, China. A numerical analysis and field data are used to verify the applicability of the proposed analytical approach. A few key influencing factors, such as the layered strata thicknesses and the characteristics of the surrounding rock are discussed. The results demonstrate that the vertical pressure increases with thickness ratio ( h 1 / h 2 ). In addition, the vertical pressure decreases with increasing internal friction angles over the range 30° to 40°, however, increases beyond 40°. The comparisons between the analytical results and the numerical results, as well as that between the analytical results and the field data exhibit good agreement, which validates the proposed analytical approach.